Top 50 Most Cited Articles on Thoracic Ossification of Posterior Longitudinal Ligament - Ding, Xing; Yan, Ming; Wu, Jinze; Xu, Chongqing; Yan, Yinjie; Yu, Zhixing; Yin, Mengchen; Xu, Jinhai; Ma, Junming; Mo, Wen (Frontiers in Surgery, 2022)
Study Design Bibliometric analysis. Objective Over the last several decades, the field of thoracic ossification of the posterior longitudinal ligament (T-OPLL) has evolved unprecedentedly, and the literature on T-OPLL has increased significantly. The purpose of this study is to identify and review the top 50 most cited publications related to T-OPLL. Methods The most frequently cited 50 articles in this field until 30 October 2021 were identified by searching Web of Science. We ranked the articles based on the citation number. Through the bibliometric method, we evaluated the following information: article title, first author, year of publication, journal of publication, total number of citations, country, and study topic. Results The number of citations of included studies ranged from 20 to 108, with a mean number of 45.4. The journal Spine published most articles (20), followed by Spinal Cord (5), and European Spine (5). All of these articles were contributed by 38 first authors, Yamazaki (4), Fujimura (3), and Aizawa (3) who published more than 2 articles. In the respect of productive countries, Japan (39) contributed most papers. Tomita contributed the most cited article in 1990 on Spine, which was the first-ever report of circumferential decompression for thoracic myelopathy due to T-OPLL. Conclusion The top 50 influential articles on T-OPLL were identified and analyzed in this study. It will undoubtedly provide a comprehensive and detailed basis for the orthopedic and neurosurgery physicians to make a clinical decision and assimilate the research focus of spine surgery.